The Role of Emotional Valence for the Processing of Facial and Verbal Stimuli—Positivity or Negativity Bias? - Kauschke, Christina; Bahn, Daniela; Vesker, Michael; Schwarzer, Gudrun (Frontiers in Psychology, 2019)
Emotional valence is predominately conveyed in social interactions by words and facial expressions. The existence of broad biases which favor more efficient processing of positive or negative emotions is still a controversial matter. While so far this question has been investigated separately for each modality, in this narrative review of the literature we focus on valence effects in processing both words and facial expressions. In order to identify the factors underlying positivity and negativity effects, and to uncover whether these effects depend on modality and age, we present and analyze three representative overviews of the literature concerning valence effects in word processing, face processing, and combinations of word and face processing. Our analysis of word processing studies points to a positivity bias or a balanced processing of positive and negative words, whereas the analysis of face processing studies showed the existence of separate positivity and negativity biases depending on the experimental paradigm. The mixed results seem to be a product of the different methods and types of stimuli being used. Interestingly, we found that children exhibit a clear positivity advantage for both word and face processing, indicating similar processing biases in both modalities. Over the course of development, the initial positivity advantage gradually disappears, and in some face processing studies even reverses into a negativity bias. We therefore conclude that there is a need for future research that systematically analyses the impact of age and modality on the emergence of these valence effects. Finally, we discuss possible explanations for the presence of the early positivity advantage and its subsequent decrease.